Beyond Biological Bonds: Child-Centered Legal Pluralism in Blended Families in Kandangan Village, East Java - Fadhilah, Nur; Zakia, Putri; Mu'allifin, M. Darin Arif; A'isyah, Siti (Universitas Islam Indonesia, 2026)
This study investigates the fulfillment of children’s rights in blended families within Indonesia’s plural legal context. It addresses three main questions: how plural legal frameworks construct the identity and rights of children in blended families, how biological assumptions embedded in statutory and religious laws limit children’s access to consistent caregiving, and how a child-centered approach can reshape legal pluralism to provide inclusive protection. Employing a qualitative socio-legal methodology, the research integrates doctrinal legal analysis with empirical data from semi-structured interviews, observations, and document analysis in five blended households in Kandangan Village, East Java. The findings show that legal definitions privileging biological lineage restrict children’s access to care, identity, and inheritance when provided by non-biological caregivers. At the same time, community-based forums such as musyawarah desa offer adaptive mechanisms that safeguard children’s welfare by validating caregiving roles beyond biological ties. Comparative insights from plural legal contexts highlight the potential of incorporating caregiving capacity and emotional bonds into formal legal frameworks to ensure the protection of children’s rights. The study concludes that advancing a child-centered legal pluralism in Indonesia requires harmonizing statutory, Islamic, and customary laws to reflect contemporary family structures while consistently prioritizing children’s rights. Its contribution lies in offering a relational and locally grounded framework for family law reform, while also identifying the limitations of single-site, small-scale research and suggesting future studies across regions and using quantitative approaches.